2020
DOI: 10.1177/0885328220922161
|View full text |Cite
|
Sign up to set email alerts
|

Marine spongin incorporation into Biosilicate® for tissue engineering applications: An in vivo study

Abstract: Biomaterials and bone grafts, with the ability of stimulating tissue growth and bone consolidation, have been emerging as very promising strategies to treat bone fractures. Despite its well-known positive effects of biosilicate (BS) on osteogenesis, its use as bone grafts in critical situations such as bone defects of high dimensions or in non-consolidated fractures may not be sufficient to stimulate tissue repair. Consequently, several approaches have been explored to improve the bioactivity of BS. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…The stretching vibrations of the N–H and CO groups of amide I (mainly the stretching vibrations of CO) and amide II (stretching of C–H and bending of N–H) cause relatively intense bands at 1630 cm −1 and 1520 cm −1 [ 38 , 39 , 40 ]. Furthermore, the amide III band extending from 1220 to 1300 cm −1 , which can be seen in the case of the spongin samples, is due to the phase combination of carbon–nitrogen bond stretching as well as N–H plane bending vibrations, considerably reducing the peptide bond (–CONH–) footprint in the spectrum of the organic/inorganic material [ 41 , 42 ]. Finally, the N–H band can be observed at 472 cm − 1 ( Figure 4 a), partially overlapping with the Fe–O band at 563 cm −1 ( Figure 4 b), leading to the lower wavenumbers of the N–H band at 461 cm −1 [ 15 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The stretching vibrations of the N–H and CO groups of amide I (mainly the stretching vibrations of CO) and amide II (stretching of C–H and bending of N–H) cause relatively intense bands at 1630 cm −1 and 1520 cm −1 [ 38 , 39 , 40 ]. Furthermore, the amide III band extending from 1220 to 1300 cm −1 , which can be seen in the case of the spongin samples, is due to the phase combination of carbon–nitrogen bond stretching as well as N–H plane bending vibrations, considerably reducing the peptide bond (–CONH–) footprint in the spectrum of the organic/inorganic material [ 41 , 42 ]. Finally, the N–H band can be observed at 472 cm − 1 ( Figure 4 a), partially overlapping with the Fe–O band at 563 cm −1 ( Figure 4 b), leading to the lower wavenumbers of the N–H band at 461 cm −1 [ 15 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biomaterials with different compositions and structure have been extensively studied for bone tissue engineering proposals. In this context, a composite material, including BS enriched with a newly marine Col was studied (Parisi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A series of experiments revealed a positive effect of sponge collagen hydrolysates on damaged or photoaged skin [270]. In addition, a recent in vivo study using rats demonstrated biocompatibility and the ability to support bone formation of biocomposites generated from collagen, isolated from A. fulva, and biosilicate [271]. Finally, powdered collagenous sponge scaffold loaded with L-cysteine hydrochlorid proved to cause a positive effect on wound healing [272].…”
Section: Marine Invertebrates Collagenmentioning
confidence: 97%
“…Furthermore, this structural protein is used for controlled drug release including antimicrobial agents such as tetracycline [270]. In another research, a potential of anticancer drug(s) loaded 3D printed patches from fish gelatin for anticancer treatment was demonstrated [271]. Due to its excellent absorption properties and the ability to resorb up to 56 days, fish collagen can be used to control wound blood bleeding [272].…”
Section: Marine Vertebrates Collagenmentioning
confidence: 99%